2008
DOI: 10.1148/radiol.2483062112
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Arthritis: Degenerative Joint Disease and Variations

Abstract: In the presence of joint space narrowing, it is important to differentiate inflammatory from degenerative conditions. The presence of osteophytes, bone sclerosis, and subchondral cysts and the absence of inflammatory features such as erosions suggest osteoarthritis. Typical osteoarthritis involves specific joints at a particular patient age. When osteoarthritis involves an atypical joint, occurs at an early age, or has an unusual radiographic appearance, then other causes for cartilage destruction should be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 13 publications
2
57
1
Order By: Relevance
“…10 The absence of spurs in people below 20 years of age correlates with the common clinical observations that are rarely a feature of degenerative joint disease in young individuals. 11 The proposed mechanical theory over the spur formation is not supported by this study as it shows that age group of people involved in maximum physical exercise from 20-40 seems to be little affected at the same time Cosentino et al has found that people involved in standing for long time as part of their professions were more likely to be affected. [12][13][14][15] Also a study reveals that chances of finding a calcaneal spur in normal population to be 15.5% and there are no clear cut relationship between the heel pain and the length, shape and direction of the calcaneal spur.…”
Section: Discussioncontrasting
confidence: 70%
“…10 The absence of spurs in people below 20 years of age correlates with the common clinical observations that are rarely a feature of degenerative joint disease in young individuals. 11 The proposed mechanical theory over the spur formation is not supported by this study as it shows that age group of people involved in maximum physical exercise from 20-40 seems to be little affected at the same time Cosentino et al has found that people involved in standing for long time as part of their professions were more likely to be affected. [12][13][14][15] Also a study reveals that chances of finding a calcaneal spur in normal population to be 15.5% and there are no clear cut relationship between the heel pain and the length, shape and direction of the calcaneal spur.…”
Section: Discussioncontrasting
confidence: 70%
“…Erosions are not typical 37 but may be found, such as in knee OA. 38,39 OA in the TMJ is also characterized by bone proliferation, but erosion is a feature as well, 36,[40][41][42] as illustrated in Figure 3.…”
mentioning
confidence: 99%
“…These indicators/ markers have been previously employed by radiography or pure optical imaging methods to detect osteoarthritis/joint rheumatism. 5,6,20,21 …”
Section: Iia Three-dimensional Quantitative Photoacoustic Imagingmentioning
confidence: 99%
“…3,4 Imaging techniques, including x-ray radiography, computed tomography (CT), ultrasonography, and magnetic resonance imaging (MRI), have been conventionally used or investigated to detect the physiologic/anatomic abnormalities in the joint cavity when OA has been established. [5][6][7][8][9][10][11][12][13][14][15][16][17] However, clinical examination remains the principal approach while these available imaging techniques are used only as supplemental methods in OA diagnosis, especially in hand OA, either because they are insensitive to the abnormal changes in the OA joint cavity or because they are too costly to be used as a routine examination method. For example, plain radiographs are conventionally used to visualize bony abnormality; however, they are insensitive to changes in soft tissues (cartilage, synovial fluid, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation